The Relationship Between Humans and Nature from the Perspective of Local Wisdom of Fishermen in Argopeni Village,Kebumen 1970-2008 - Romadi; Laily Fu'adah (Journal of Indonesian History, 2025)
Indonesia is an archipelagic nation with a coastline spanning over 81,000 km. Along this coastline reside communities earning their livelihoods as fishermen, including those in Argopeni Village, Kebumen Regency. The geographical environment of Argopeni Village consists of limestone mountains jutting into the Indian Ocean in the western part of Kebumen Regency. The lives of Argopeni fishermen, generally characterized by economic hardship, are lived with simplicity and grounded in local values, relying on trust and honesty as their capital. To sustain their livelihoods, the fishermen of Pedalen Beach in Argopeni Village firmly uphold traditions related to their environment, particularly those concerning the myth of Nyai Roro Kidul. These traditions include observing sacred fishing days, performing sea offering ceremonies (sedekah laut) and rituals, and strictly avoiding the taboos associated with Nyai Roro Kidul. By adhering to these traditions, the fishermen maintain a harmonious life. Furthermore, to align their daily needs with their working environment, the fishermen have adapted to the marine conditions. Through this adaptation, they possess the skills and wisdom necessary for maritime activities, given the high risks associated with fishing at sea. Their capabilities include identifying fishing seasons, locating fish aggregations, and assessing sea conditions before setting sail.